ANALISIS FAKTOR PENYEBAB KECELAKAAN LALULINTAS SEBAGAI ACUAN PERENCANAAN JALAN UNTUK MENINGKATKAN KESELAMATAN - Gita Puspa Artiani (FORUM MEKANIKA, 2016)
The highway where the planning and manufacturing, to provide safety, comfort, safety and efficiency, but there's also the incidence of traffic accidents on the highway. By looking at the large number of accidents in Indonesia's road safety must be viewed comprehensively on all aspects of planning, the work of making a road which is the design direction and visualization of trace roads for the road meet the requirements of safe, secure, comfortable, efficient. The purpose of this study was to determine the factors that cause potential traffic accidents linked to road planning so as to provide proposals and suggestions relating to the improvement of traffic safety in order to reduce the accident rate in terms of planning the road. This study begins with identifying the causes of traffic accidents with survey method / descriptive. Were analyzed with SPSS version 21 to find a relationship between a number of variables of the potential causes of traffic accidents were originally mutually independent of each other, namely human variables (the driver), vehicle, road and environment, so that it can be made one or more sets of variables are dominant of the number of initial variables. As a case study, a study conducted diruas road Ciasem - Pamanukan Subang Regency, West Java. Results of the study are three major types of cross-sectional ranking of frequent road accidents by type of vehicle and the factors that cause accidents often occur, as follows: 1) .Types sectional intersection cornering, 2) .Types cross section of straight road intersection and 3 ) .Jalan straight amid residential or public facilities.